Frequency and Clinical-Laboratory complications in patients with alcoholic intoxication treated in emergency of the Hospital III Goyeneche. Arequipa 2018. - Yubica Allison León-Ramos (2021)
This study is aimed at describing the frequency and complications clinical-laboratory of patients with alcoholic intoxication treated in the emergency service of Hospital III Goyeneche, during 2018. Material and Methods: An observational, retrospective design was carried out and transversal, obtaining the required information through a data collection form. The data collection sheets were filled taking information from existing clinical records to perform statistical analysis and interpretation of data. Results: It was studied 527 cases, noting that 81.6 % was male. The (53.5%) cases were between 15 and 30 years old. 74.8% went to medicine, followed by 24.5% who went treated in surgery. The (88.4%) cases of alcoholic intoxication presented clinical-laboratory complications. Regarding clinical-laboratory complications, neurological complications (57.9%) predominated, highlighting the alteration of consciousness. The time of observation was less than 24 hours (98.7%). Conclusion: It was established that alcohol intoxication has an important prevalence among men treated in the Emergency service, and the most frequent type of clinical-laboratory complication was neurological complications.